High maternal-fetal HLA eplet compatibility is associated with severe manifestation of preeclampsia - Stefańska, Katarzyna; Kurkowiak, Małgorzata; Piekarska, Karolina; Chruściel, Elżbieta; Zamkowska, Dorota; Jassem-Bobowicz, Joanna; Adamski, Przemysław; Świątkowska-Stodulska, Renata; Abacjew-Chmyłko, Anna; Leszczyńska, Katarzyna; Zieliński, Maciej; Preis, Krzysztof; et al. (Frontiers in Immunology, 2023)
Introduction Preeclampsia is responsible for more than 70 000 and 500 000 maternal and fetal deaths, respectively each year. Incomplete remodelling of the spiral arteries in placenta is the most accepted theory of preeclampsia pathogenesis. However, the process is complexed with immunological background, as pregnancy resembles allograft transplantation. Fetus expresses human leukocyte antigens (HLA) inherited from both parents, thus is semiallogeneic to the maternal immune system. Therefore, induction of fetal tolerance is crucial for physiological outcome of pregnancy. Noteworthy, the immunogenicity of discordant HLA antigens is determined by functional epitopes called eplets, which are continuous and discontinuous short sequences of amino acids. This way various HLA molecules may express the same eplet and some HLA incompatibilities can be more immunogenic due to different eplet combination. Therefore, we hypothesized that maternal- fetal HLA incompatibility may be involved in the pathogenesis of gestational hypertension and its progression to preeclampsia. We also aimed to test if particular maternal-fetal eplet mismatches are more prone for induction of anti- fetal HLA antibodies in gestational hypertension and preeclampsia. Methods High resolution next-generation sequencing of HLA-A, -B, -C, -DQB1 and -DRB1 antigens was performed in mothers and children from physiological pregnancies (12 pairs) and from pregnancies complicated with gestational hypertension (22 pairs) and preeclampsia (27 pairs). In the next step HLA eplet identification and analysis of HLA eplet incompatibilities was performed with in silico approach HLAMatchmaker algorithm. Simultaneously maternal sera were screened for anti-fetal HLA class I, class II and anti-MICA antibodies with Luminex, and data were analyzed with HLA-Fusion software. Results We observed that high HLA-C, -B, and DQB1 maternal-fetal eplet compatibility was associated with severe preeclampsia (PE) manifestation. Both quantity and quality of HLA epletmismatches affected the severity of PE. Mismatches in HLA-B eplets: 65QIA+76ESN, 70IAO, 180E, HLA-C eplets: 193PL3, 267QE, and HLA-DRB1 eplet: 16Y were associated with a mild outcome of preeclampsia if the complication occurred. Conclusions High HLA-C, HLA-DQB1 and HLA-B eplet compatibility between mother and child is associated with severe manifestation of preeclampsia. Both quantity and quality of maternal-fetal HLA eplet mismatches affects severity of preeclampsia.